2018
DOI: 10.3390/su10103765
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Algorithm-Optimized Long Short-Term Memory Network for Stock Market Prediction

Abstract: With recent advances in computing technology, massive amounts of data and information are being constantly accumulated. Especially in the field of finance, we have great opportunities to create useful insights by analyzing that information, because the financial market produces a tremendous amount of real-time data, including transaction records. Accordingly, this study intends to develop a novel stock market prediction model using the available financial data. We adopt deep learning technique because of its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
158
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(167 citation statements)
references
References 54 publications
1
158
0
8
Order By: Relevance
“…In recent years, with the significant advances in deep learning techniques, recurrent neural networks have emerged as a promising model for handling sequential data in various tasks such as natural language processing, speech recognition, and computer vision. Moreover, several studies proved that RNN including LSTM cells is the most useful model in the financial time series prediction problem [30][31][32][33][34][35][36]. For example, Chen et al [30] introduced a stock price movement prediction model based on LSTM.…”
Section: Stock Market Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, with the significant advances in deep learning techniques, recurrent neural networks have emerged as a promising model for handling sequential data in various tasks such as natural language processing, speech recognition, and computer vision. Moreover, several studies proved that RNN including LSTM cells is the most useful model in the financial time series prediction problem [30][31][32][33][34][35][36]. For example, Chen et al [30] introduced a stock price movement prediction model based on LSTM.…”
Section: Stock Market Predictionmentioning
confidence: 99%
“…They concluded that LSTM could attain satisfactory performance in predicting China's index price movements. Chung and Shin [34] employed an LSTM network to predict KOSPI index prices in the next day. They tested their method on KOSPI index data from 2000 to 2016 and found that the method achieved satisfactory performance.…”
Section: Stock Market Predictionmentioning
confidence: 99%
“…Unlike LTMA, LSTM introduces cells and gates to form a "highway" to retain gradient information in a long sequence of a recurrent neural network. In [46], a genetic algorithm was integrated with an LSTM network to optimize time window size and architectural factors, to better predict the Korea Composite Stock Price Index.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, to add realistic assumptions to the current stock, such as transaction costs, liquidity issues, and bid and spread basis, Meng and Khushi [38] suggested using a reinforcement learning model in financial markets to enhance the current models in the field. Moreover, optimization algorithms are used with artificial intelligent prediction models to improve the efficiency of the predications in addition to enhancing the computation complexity [39,40]. Moreover, many methods in the literature suggested using different models to improve the prediction model of financial markets, namely neural network [41] and Markov chain [42] in addition to evaluating different machine learning models as discussed in [43].…”
Section: Introductionmentioning
confidence: 99%